1995
DOI: 10.1016/0014-5793(95)00915-v
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrine chaperone 7B2 can enhance in vitro POMC cleavage by prohormone convertase PC2

Abstract: . Based on its functional characteristics and the finding that the N-terminal half of 7B2 is distantly related to members of the Hsp60 family of chaperones, 7B2 has been referred to as a neuroendocrine chaperone [17]. In vitro, the recombinant intact form of 7B2 (and not its processed form) inhibits PC2 convertase activity and blocks autocatalytic conversion of proPC2 into its mature form [24,25]. These observations indicate that intact 7B2 regulates PC2 activity in neuroendocrine cells by preventing premature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…We now demonstrate the expression of the following three additional neuroendocrine markers found in the ciliary epithelium: (1) the prohormone convertases PC 1 and PC2, which have been shown to intervene in the processing of the precursor of NT and its related peptide neuromedin N (NN), pro-NT/NN; and (2) we provide evidence that 7B2, a neuroendocrine polypeptide involved in the regulation of the enzymatic activity and maturation of PC2 (Braks and Martens, 1995;Zhu and Lindberg, 1995) is also expressed in the ocular ciliary epithelium. The expression of these molecular markers provides new information relevant to the differentiated neuroendocrine phenotype of the ciliary epithelium and establishes a firm working framework to investigate the role of regulatory peptides synthesized and released by the ciliary epithelium in the regulation of aqueous humor secretion and/or TOP.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…We now demonstrate the expression of the following three additional neuroendocrine markers found in the ciliary epithelium: (1) the prohormone convertases PC 1 and PC2, which have been shown to intervene in the processing of the precursor of NT and its related peptide neuromedin N (NN), pro-NT/NN; and (2) we provide evidence that 7B2, a neuroendocrine polypeptide involved in the regulation of the enzymatic activity and maturation of PC2 (Braks and Martens, 1995;Zhu and Lindberg, 1995) is also expressed in the ocular ciliary epithelium. The expression of these molecular markers provides new information relevant to the differentiated neuroendocrine phenotype of the ciliary epithelium and establishes a firm working framework to investigate the role of regulatory peptides synthesized and released by the ciliary epithelium in the regulation of aqueous humor secretion and/or TOP.…”
mentioning
confidence: 74%
“…Finally, the expression of 7B2, a neuroendocrine polypeptide involved in the regulation of the enzymatic activity of PC2 and its maturation (Braks and Martens, 1995;Zhu and Lindberg, 1995), provides a firm molecular demonstration that the human ciliary epithehum is neuroendocrine in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Its prior processing might be required to allow proPC2 cleavage. Thus when supplemented to a cell-free translation lysate derived from Xenopus intermediate pituitary cells, mature 7B2, but not its unprocessed precursor, could stimulate PC2-mediated processing of POMC [100]. In the same vein, a processing-resistant mutant form of pro7B2, unlike the native form, was unable to promote the conversion of proPC2 into PC2 in mouse corticotroph AtT-20\PC2-transfectant cells [88].…”
Section: B2 Regulates Pc2 Activationmentioning
confidence: 95%
“…Endoproteases may be affected and regulated by endogenous factors in vivo, which may be cell and species specific; these factors can either increase or inhibit processing of protein precursors. In that respect, it has recently been demonstrated that the intact form of the neuroendocrine-specific polypeptide 7B2 is a potent inhibitor of PC2 but not PCI (Martens, Braks, Eib, Zhou & Lindberg, 1994), while processed 7B2 stimulates Wulff et al (1993) POMC cleavage in vitro, probably activating PC2 (Braks & Martens, 1995). Also, changes in intracellular conditions, such as pH and Ca2+ concentration, might modulate endoproteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In that respect, it has recently been demonstrated that the intact form of the neuroendocrine-specific polypeptide 7B2 is a potent inhibitor of PC2 but not PCI (Martens, Braks, Eib, Zhou & Lindberg, 1994), while processed 7B2 stimulates Table 2. Examples of eukaryotic proteases which cleave precursors of secretory peptides endoproteolytically POMC cleavage in vitro, probably activating PC2 (Braks & Martens, 1995 (Guttman & Boissonnas, 1961;Bradbury, Finnie & Smyth, 1982;Akil, Shiomi & Matthews, 1985;Birch, Estivariz, Bennett & Loh, 1991 (Hurtley, Bole, Hoover-Litty, Helenius & Copeland, 1989;Cool, Fenger, Snell & Loh, 1995). It has been demonstrated that N-linked glycosylated residues may reduce endoproteolysis of N-POMC(1I77) (Birch et al 1991) and prorenin (Ladenheim, Seidah & Rougeon, 1991), although another report demonstrated that glycosylation does not play a significant role in POMC endoproteolysis (Noel, Keutmann & Mains, 1991 Hormones and neuropeptides need to be exported from the cells in which they are synthesized in order to reach their target tissues and exert their biological actions; for this reason targeting, sorting and secretion of hormones and neuropeptides is a carefully controlled mechanism within endocrine and neuronal cells.…”
mentioning
confidence: 99%